Padrões de morbidade em assistência primária na região de Ribeirão Preto, SP (Brasil) Health care morbidity levels in the region of Ribeirão Preto, SP (Brazil) - Juan Stuardo Yazlle Rocha; Jarbas Leite Nogueira (Universidade de São Paulo, 1985)
São apresentados os resultados obtidos com a implantação de um sistema de agendamento de casos, para consulta médica, em quatro serviços ambulatoriais e que constitui, ao mesmo tempo, o instrumento de referência de dados de morbidade. As estatísticas de morbidade ambulatorial adquirem grande valor se o serviço atende a toda a demanda e se há boa cobertura populacional. Crianças, mulheres e velhos constituíram a maior demanda assistencial destes serviços. Destacaram-se como os diagnósticos mais freqüentes as doenças infecciosas e parasitárias, doenças do aparelho respiratório, inflamações do olho e ouvido, doenças da pele e do tecido subcutâneo e do aparelho geniturinário. Estes problemas refletem as condições de vida, os problemas de saúde mais freqüentes das populações atendidas e a política de assistência dos serviços estudados. Results obtained from a system of appointments for medical consultation in four health centers are presented, This system also serves as system of reference for morbidity data. The ambulatory morbidity data are most valuable if the service meets all the demand and if there is good population coverage, Knowledge about the health policy of the clinics, such as health programs for women and children and for special diseases or problems is important for an adequate understanding of the demand profile. The clinics included in the study were municipal and academic health centers, with unrestricted access. Women and children and elderly people made up the majority of those seeking the health service. The most frequent causes of medical assistance were the following: parasitic diseases, diseases of the respiratory system, inflammatory diseases of the eye and ear, skin and subcutaneous tissue diseases and infections of the genito-urinary system, in that order. There was great similarity between the morbidiy profile registered at the different centers, located in different cities and stability of morbidity profile was observed throughtout the study period. Problems referred to are related to the living conditions in the respective areas and to the health policy at the centers researched.